2019
DOI: 10.1111/syen.12343
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of the arctiine tribe Syntomini (Lepidoptera, Erebidae)

Abstract: The Old World tribe Syntomini is the most neglected of the three major groups of the subfamily Arctiinae -the most megadiverse lineage (c. 11 000 species) of the superfamily Noctuoidea, comprising about a quarter of its entire species diversity. In none of the previous morphogenetic studies was Syntomini (which are often conspicuously spotted, aposematic moths) sampled adequately enough to provide information about the tribe's systematic diversity and relationships above species level. As such data are of cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…However, more samples of S. nigricornis and other middle-eastern taxa are needed to resolve the biogeographic history of this connection. Finally, the weak support values recovered for the relationship of S. phegea and S. aequipuncta with the lineages of quercii-marjana and ragazzii-nigricornis stress the need to broaden the analysis to more genetic markers and species to fully resolve the evolutionary history of Western Palaearctic Syntomis (see also Przybyłowicz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, more samples of S. nigricornis and other middle-eastern taxa are needed to resolve the biogeographic history of this connection. Finally, the weak support values recovered for the relationship of S. phegea and S. aequipuncta with the lineages of quercii-marjana and ragazzii-nigricornis stress the need to broaden the analysis to more genetic markers and species to fully resolve the evolutionary history of Western Palaearctic Syntomis (see also Przybyłowicz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The p-distance between barcode sequences was calculated in MEGA X ( Kumar et al, 2018 ). The outgroup sequence of Fletcherinia decaryi Griveaud, 1964 (GenBank accession code ) was obtained from the study of Przybyłowicz et al (2019) . DNA sequences are deposited in GenBank ( – ) and accession codes are provided in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…belong to a single evolutionary lineage deriving from a megadiverse radiation, which also gave raise to what have been interpreted as out-of-Madagascar dispersal events, reaching Africa ( Pseudonaclia puella ( Boisduval, 1847 )), Mauritius and even the Palaearctic (genus Dysauxes ) ( Przybyłowicz et al, 2019 ; Przybyłowicz et al, 2021, unpublished data). However, since the “Amatidae” monograph of Griveaud (1964) , little attention has been paid to the systematics and biogeography of the group, with only a few additional species described by P. Griveaud and P. Viette that were listed in Viette (1990) , until the phylogenetic paper of Przybyłowicz et al (2019) . The latter paper and our further examinations show that the present systematic arrangement comprises several genera which are artificial assemblages of not closely related species rather than evolutionary monophyletic units.…”
Section: Introductionmentioning
confidence: 96%
“…In this study we follow the systematic account of Przybyłowicz et al (2019) for the higher taxonomic levels.…”
Section: Methodsmentioning
confidence: 99%
“…Following morphological and molecular studies of the entire Noctuoidea it was downgraded to tribal rank by Jacobson & Weller (2002) and fi nally treated as a subtribe Thyretina of Syntomini (Zahiri et al, 2011). Recently a comprehensive molecular study revealed that the Thyretina is not monophyletic (Przybyłowicz et al, 2019). As a result, it was formally synonymized with Syntomini.…”
Section: Introductionmentioning
confidence: 99%